Scientific Substantiation of Introduction of Systems of Small-Intensive Irrigation Under Conditions of Mineral Farming in Azerbaijan - Aliyev, RAE. Z.H. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2019)
The study of the world experience and the results of long-term experiments with drip irrigation systems in the Republic in various climatic and soil conditions shows that the creation of irrigation systems of this type is effective and economically profitable when irrigation of various perennial plantations, vegetable, tilled crops, ornamental plantations, nurseries etc. Drip irrigation has almost universal application, in particular, it is applicable where other methods of irrigation can not be used or ineffective: With a complex relief and a large slope of the site (up to 45 degrees or more); In areas with prolonged droughts and constant strong winds; For local water sources with a relatively limited amount of water; On soils with low power and very low or high hygroscopicity; On soils prone to salinity; When used for irrigation of water with a high content of water-soluble salts, etc.